Ilustración Nariñense [Nariñense Illustration], the cultural magazine of the Colombian south 1924-1955 (2016)
This article presents Ilustración Nariñense [Nariñense Illustration], a cultural magazine of the first half of the XX c., edited in Pasto for more than three decades. This publication achieved an important role in the construction of a collective imaginary about the progress of the region, and its attempt to overcome geographic isolation. The editorial aim of this publication was to become an instrument for the establishment of a common project for regional transformation, through the struggle to install a transport system, that enabled communication with the interior of the country as well as with other countries; under the assumption that the progress of the region was linked to the construction of a railroad. The magazine´s journalistic work and essays attempted to break with the intellectual isolation of the area, and to promote the circulation of regional interests and problems. Material and content aspects were examined for the study of this publication. This implied the construction of thematic and chronological indexes, as well as a hermeneutic analysis of its articles, allowing for the interpretation of the axes that structured the magazine.